Systematic investigation of twist generation and propagation in a modified ring spinning system - Yin, Rong; Tao, Xiao-Ming; Xu, Bin-gang (Textile research journal, 2020)
Twisting is an important process used to form a continuous yarn from short staple fibers and to determine the structure and properties of the resultant yarn. This paper systematically examines the yarn twisting process in a modified ring spinning process based on a theoretical model proposed recently. To reduce the number of experiments, response surface methodology (RSM) involving a central composite design (CCD) in three factors—twist multiplier, speed ratio and wrap angle—was successfully employed for the study and analysis. The significant terms of the models were studied, and it was discovered that the speed ratio and wrap angle are statistically significant for the responses of twist efficiency, propagation coefficients of twist trapping, and congestion. More importantly, linear relationships were found among the three responses.